"I am willing to do both well": Chinese academic mothers facing tension in family and career. - Bao, Li; Wang, Guanghua (Frontiers in psychology, 2022)
Academic mothers perform intersected roles. They carry out their profession in workplaces, while they take the "second shift" of motherhood back to their families. The contested expectations in family and career built by the heterosexual matrix cause tension to academic mothers. We qualitatively investigate the interview data of six Chinese women academics on how they perform to negotiate their motherhood and academic work in the context of Chinese higher education, driven by the Butlerian theoretical concept of the heterosexual matrix. The findings suggest that Chinese academic mothers play a zero-sum game between being mothers and being academics, deriving from their ontological responsibilities of motherhood. We conclude that in the masculine academia, these women academics help maintain the heterosexual matrix by satisfying the gender normativity when they negotiate their performances in their family and career; meanwhile, most have developed some strategies to achieve their career advancement.; Competing Interests: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest. (Copyright © 2022 Bao and Wang.)
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; chine; conciliation famille-travail; famille; femmes* universitaires; hétérosexisme; maternité; matrice hétérosexuelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail

“I have no room of my own”: COVID-19 pandemic and work-from-home through a gender lens - Chauhan, Priyanshi (Gender Issues, 2022)
Working from home is not gender neutral. As the COVID-19 pandemic has relocated all non-essential work to the home setting, it becomes imperative to examine the phenomenon through a gender lens. Accordingly, I conducted a qualitative study using semi-structured interviews with 30 dual-earning married couples in India to study the gendered work-from-home experiences of men and women during the pandemic. The findings suggest that the pandemic has disproportionately increased the burden of unpaid work for women as compared to men. Women are negotiating gendered time–space arrangements within their households with the allocation of limited resources being in favor of men. When this interacts with work, gender inequalities are reinforced both at work and home. Gender roles and unpaid work determine women’s choices regarding when and where to work, boundary management between work and non-work domains, and their experiences of social isolation. Further, gender roles have also affected women’s decisions regarding returning to work post-pandemic, where some women may not be returning to work at all. Finally, the paper identifies how gender intersects with the existing conceptual frameworks of working from home, and makes a strong case for integrating gender considerations in the work-from-home policies. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; conciliation famille-travail; covid-19; famille; hétérosexisme; inde; inégalités; inégalités hommes-femmes; pandémie; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; travail gratuit

Homoparentalités, état des lieux - Gross, Martine; Association des parents et futurs parents gays et lesbiens; Colloque Parentés et différence des sexes (Érès, 2005)
«Bourdieu avait déjà considéré que la famille, loin d'être une "donnée immédiate de la réalité sociale" était en fait "un instrument de construction de cette réalité". Quelle signification donner alors au présent ouvrage consacré aux familles homoparentales ? Il y a dans cet intitulé l'expression d'une revendication qui a pris toute sa force au cours des dernières décennies : celle de pouvoir être parent et homosexuel, cette revendication étant indissociable de l'aspiration à constituer une famille comme les autres. C'est bien dans ce mouvement que s'inscrit cet ouvrage, militant au meilleur sens du terme. L'objectif est en effet l'existence dans l'espace public d'un fait social dans toute sa complexité, c'est-à-dire avec la volonté d'un traitement raisonnable (au sens de faire appel à la raison) fondé sur un recours intensif aux sciences de l'homme.Distinguer la procréation de la sexualité et considérer que le couple conjugal et parental peut ne pas être fondé sur la différence des sexes, ceci tout en revendiquant le droit au label "famille", c'est consacrer le fait que la famille ne s'impose plus aux individus comme une institution immuable à laquelle il n'ont comme choix que celui de s'ajuster ; ils se donnent désormais le droit de concevoir l'organisation de leur univers privé en fonction de leurs propres aspirations et en référence à des valeurs qui prétendent relever tout autant de l'intérêt général que de celui des enfants éventuellement concernés.» Jacques CommailleRendant compte des études théoriques sur la parenté et des recherches sociologiques, ethnologiques, anthropologiques, juridiques et cliniques sur les familles homoparentales et leurs enfants, cette nouvelle édition, revue, mise à jour et augmentée, constitue une référence incontournable pour aborder les interrogations suscitées aujourd'hui par la très controversée question de l'homoparentalité.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; famille; france; hétérosexisme; identités LGBTQIA2+; maternité; parentalité; postmodernisme; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques